THIERISH SKIN GRAFTING IN COMPLEX PATIENTS- CASE REPORT - Gadzevska Tomulevska, Ilina; Mitev, Konstantin; Taushanov, Mihail (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
We present a patient which is complex patient regarding the risks for skin graft survival. Multidisciplinary management of the risks is the only way of skin grafting survival. Choosing the right time, right donor region, right techniques of harvest the skin grafts, choice and preparation of graft, fixation techniques, good preparation of the recipient region and controlling the chronic diseases which are bringing risks such as Diabetes mellitus, arteriosclerosis, vascular diseases, infection, are the key of surviving the skin graft. Keywords :  Autologous skin grafts, complex patient, skin graft survival.